2017
DOI: 10.6061/clinics/2017(12)07
|View full text |Cite
|
Sign up to set email alerts
|

Pain and quality of life in breast cancer patients

Abstract: OBJECTIVE:To evaluate the influence of pain on quality of life in breast cancer patients.METHODS:A cross-sectional study of 400 patients, including 118 without metastasis, 160 with loco-regional metastasis and 122 with distant metastasis. The instruments used were the European Organization for Research and Treatment for Cancer Quality of Life Questionnaire-Core 30 and the Breast Cancer-specific 23 and short McGill Pain Questionnaire.RESULTS:In total, 71.7% of patients reported pain. The most frequent sensory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 37 publications
2
40
1
24
Order By: Relevance
“…Furthermore, the hypothesized item‐scale correlations were higher than the alternatives, indicating that the items in the diverse scales measured distinct aspects of HRQoL; this supports the discriminant validity of the SF‐36v2. Related previous studies obtained comparable results with the same scales …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the hypothesized item‐scale correlations were higher than the alternatives, indicating that the items in the diverse scales measured distinct aspects of HRQoL; this supports the discriminant validity of the SF‐36v2. Related previous studies obtained comparable results with the same scales …”
Section: Discussionsupporting
confidence: 81%
“…The ceiling effect in the BP scale suggests that bodily pain was not a major physical problem among patients in this study; however, this finding would need further confirmation. Previous related studies with samples of patients with breast cancer have shown that pain is still a major influencing factor during treatment and rehabilitation process in breast cancer patient populations . Replicating this finding would help confirm whether the BP scale can adequately capture the full range of physical pain responses and detect changes in bodily pain over the time since diagnosis and the treatment process.…”
Section: Discussionmentioning
confidence: 72%
“…In our cohort, BPI "worst pain" was moderate/severe for 42% of patients, and "pain interference" was moderate/severe for 80% of patients. Increased pain severity has been associated with a worse HRQoL or health status in patients with advanced breast cancer [14,40,45]. However, patient-reported pain/discomfort was not an independent predictor of HRQoL in our regression analysis despite a high proportion (~70%) of the EU5 patients in our analysis reporting some/ extreme problems in the EQ-5D-3L domain of pain/discomfort.…”
Section: Discussioncontrasting
confidence: 52%
“…Pain was associated with lower FWB and the total quality of life scores compared to other symptoms (p=0.036, for both). Costa et al, (2017) conducted a study to evaluate the influence of pain on QoL in BC patients and concluded that pain compromises the QoL of BC patients, particularly those with advanced stages of the disease.…”
Section: Discussionmentioning
confidence: 99%